Service fairness and IS continuance model in cloud computing. (1st January 2014) - Lawkobkit, Montri; Speece, Mark
This study integrates service fairness into a post-acceptance model of information system continuance. This study added constructs based on Greenberg's (1993) four-component taxonomy of organisational justice. The research model seeks to be useful in predicting post-acceptance satisfaction, which enhances continued usage of services together with a technological product. The results show that perceived usefulness and satisfaction influence continuance intention, as the post-acceptance model predicts. Three of the four distinct service fairness dimensions, systemic, configural and interpersonal fairness significantly enhanced post-acceptance satisfaction. However, the relationship between informational fairness and satisfaction was negative and significant.